2017
DOI: 10.2147/jpr.s150857
|View full text |Cite
|
Sign up to set email alerts
|

Current methodological approaches in conditioned pain modulation assessment in pediatrics

Abstract: Conditioned pain modulation (CPM) paradigms have been used in various studies with healthy and non-healthy adult populations in an attempt to elucidate the mechanisms of pain processing. However, only a few studies so far have applied CPM in pediatric populations. Studies finding associations with chronic pain conditions suggest that deficiencies in underlying descending pain pathways may play an important role in the development and persistence of pain early in life. Twelve studies were identified using a Pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…The present study also compared inhibitory pain modulation capabilities, using the CPM paradigm, between adolescents with migraine and healthy adolescents. Previous studies on CPM responses found reduced inhibitory efficacy in youth with chronic pain such as irritable bowel syndrome, functional abdominal pain, and musculoskeletal pain, compared to healthy controls 45 . For migraine patients, our group has published the only study to date comparing CPM responses between adolescents with migraine and healthy adolescents.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The present study also compared inhibitory pain modulation capabilities, using the CPM paradigm, between adolescents with migraine and healthy adolescents. Previous studies on CPM responses found reduced inhibitory efficacy in youth with chronic pain such as irritable bowel syndrome, functional abdominal pain, and musculoskeletal pain, compared to healthy controls 45 . For migraine patients, our group has published the only study to date comparing CPM responses between adolescents with migraine and healthy adolescents.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies on CPM responses found reduced inhibitory efficacy in youth with chronic pain such as irritable bowel syndrome, functional abdominal pain, and musculoskeletal pain, compared to healthy controls. 45 For migraine patients, our group has published the only study to date comparing CPM responses between adolescents with migraine and healthy adolescents. No differences between the groups were found in CPM responses, which were evoked using 2 paradigms (heat and pressure as the test stimuli).…”
Section: Discussionmentioning
confidence: 99%
“…Conditioning reduces pain sensitivity (i.e. evokes descending inhibition) but impaired CPM (reduced degree of inhibition and/or facilitation) is common in patients with chronic pain [41] . CPM was impaired in adolescents with scoliosis, many of whom also reported neuropathic pain descriptors [42] and in adolescents with peripheral neuropathic pain [8] .…”
Section: Assessmentmentioning
confidence: 99%
“… 21 , 24–28 Studies in the pediatric population using dynamic QST (ie, focusing on the evaluation of pain modulation) have shown that chronic pain conditions are associated with altered excitatory and inhibitory endogenous pain modulation systems. 10 , 15 , 29–36 The endogenous inhibitory pathways of pain modulation can be indirectly assessed using the CPM paradigm. 29 , 37 Assessing CPM in a clinical setting may be a valuable tool to assess any deficits in the descending inhibitory pain response found in some chronic pain conditions such as abdominal pain and chronic musculoskeletal pain in youth when compared to healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“… 10 , 15 , 29–36 The endogenous inhibitory pathways of pain modulation can be indirectly assessed using the CPM paradigm. 29 , 37 Assessing CPM in a clinical setting may be a valuable tool to assess any deficits in the descending inhibitory pain response found in some chronic pain conditions such as abdominal pain and chronic musculoskeletal pain in youth when compared to healthy controls. 10 , 30 , 33 , 38 , 39 The endogenous facilitatory phenomenon of pain modulation such as temporal summation has been shown to be involved in the development of some chronic pain conditions such as sickle cell disease, fibromyalgia, migraines, and functional abdominal pain.…”
Section: Introductionmentioning
confidence: 99%